Contribution of Petty Trade on Household Income and Poverty Reduction - Khatiwada, Sita Kumari (Dristikon: A Multidisciplinary Journal, 2019)
The study aims to explore the contribution of petty trade on household income and poverty reduction. For this purpose, forty respondents engaged in petty trade were selected in Dharan city in different petty markets like Chhata Chowk, Vanu Chowk and Purano Bazar in Dharan city. The required information was collected through the interview by using a structured interview schedule, observation, and focused group discussion. This study employed both judgmental sampling to obtain the sample. The program used in data analysis is the Statistical Package for Social Science (SPSS) program to obtain frequencies in table and figure and ANOVA and correlation for the hypothetical test. Descriptive statistics is carried out to analyze the contribution of petty trade on household income and poverty reduction. The researcher has analyzed age, gender, religion, came from education level, marital status, types of commodity, types of consumer, attitude of consumer, attitude of society, sources of commodity, amount of investment, improvement in economic condition, payment of tax, amount of tax, office to be paid tax, fulfillment of needs, reduction of poverty and portion of household income of respondents. According to respondents, petty trade is their main source of income. Hence, it has brought a qualitative change in household income and poverty reduction of respondents.